Genetic diversity and antimicrobial resistance profiles of Staphylococcus pseudintermedius associated with skin and soft-tissue infections in companion animals in Lisbon, Portugal - Morais, Catarina; Costa, Sofia Santos; Leal, Marta; Ramos, Bárbara; Andrade, Mariana; Ferreira, Carolina; Abrantes, Patrícia; Pomba, Constança; Couto, Isabel (Frontiers in Microbiology, 2023)
Staphylococcus pseudintermedius is the main bacterial pathogen of skin and soft-tissue infections (SSTIs) in companion animals. Antimicrobial resistance in this species is a growing public health concern. This study aims to characterize a collection of S. pseudintermedius causing SSTIs in companion animals, establishing the main clonal lineages and antimicrobial resistance traits. The collection corresponded to all S. pseudintermedius (n=155) causing SSTIs in companion animals (dogs, cats and one rabbit) collected between 2014 and 2018 at two laboratories in Lisbon, Portugal. Susceptibility patterns were established by disk diffusion for 28 antimicrobials (15 classes). For antimicrobials without clinical breakpoints available, a cut-off value (COWT) was estimated, based on the distribution of the zones of inhibition. The blaZ and mecA genes were screened for the entire collection. Other resistance genes (e.g. erm, tet, aadD, vga(C), dfrA(S1)) were searched only for those isolates showing an intermediate/resistance phenotype. For fluoroquinolone resistance, we determined the chromosomal mutations in the target genes grlA and gyrA. All the isolates were typed by PFGE following SmaI macrorestriction and isolates representative of each PFGE type were further typed by MLST. Forty-eight out of the 155 S. pseudintermedius isolates (31.0%) were methicillin-resistant (mecA+, MRSP). Multidrug-resistant (MDR) phenotypes were detected for 95.8% of the MRSP and 22.4% of the methicillin-susceptible (MSSP) isolates. Of particular concern, only 19 isolates (12.3%) were susceptible to all antimicrobials tested. In total, 43 different antimicrobial resistance profiles were detected, mostly associated with the carriage of blaZ, mecA, erm(B), aph3-IIIa, aacA-aphD, catpC221, tet(M) and dfr(G) genes. The 155 isolates were distributed within 129 PFGE clusters, grouped by MLST in 42 clonal lineages, 25 of which correspond to new sequence types (STs). While ST71 remains the most frequent S. pseudintermedius lineage, other lineages that have been replacing ST71 in other countries were detected, including ST258, described for the first time in Portugal. This study revealed a high frequency of MRSP and MDR profiles among S. pseudintermedius associated with SSTIs in companion animals in our setting. Additionally, several clonal lineages with different resistance profiles were described, evidencing the importance of a correct diagnosis and selection of the therapy.